Real-world evaluation of prevalence, cohort characteristics, and healthcare utilization and expenditures among adults and children with autism spectrum disorder, attention-deficit hyperactivity disorder, or both - Amanda L. Zaleski; Kelly J. Thomas Craig; Raiha Khan; Rebecca Waber; Wei Xin; Makia Powers; Una Ramey; Dorothea J. Verbrugge; Deborah Fernandez-Turner (BMC Health Services Research)
Abstract Background Autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD) are among the most common neurodevelopmental disorders. However, significant gaps persist in understanding health and healthcare-related needs of individuals diagnosed with ASD and/or ADHD across the lifespan. Thus, this real-world evaluation sought to characterize the prevalence of ASD, ADHD, and co-existing ASD and ADHD (AuDHD); sociodemographics; frequent comorbidities and co-occurring diagnoses; and healthcare utilization and expenditures among members of a large national payor. Methods This study represents an observational, cross-sectional evaluation of claims from a large national payor. Retrospective claims analyses of commercial fully insured (C-FI) members from 1/1/2022–12/31/2022 identified diagnoses for ASD and/or ADHD among adults (≥ 18 year) and children (< 18 year). Chi-squared tests, T-tests, and Fisher’s exact tests examined between-group differences in sociodemographic, health, and healthcare-related measures among members with neurodevelopmental disorders compared to members without ASD and/or ADHD. Results Within adults (N = 1,928,106), 4.2% of members (60.2% White, 52.9% female, mean age: 34.1 ± 10.9 year) were diagnosed with neurodevelopmental disorders: ADHD (4.0%, n = 76,515); ASD (0.1%, n = 2,134); or AuDHD (0.1%, n = 1,266) (all P < 0.0001). Within children (N = 464,749), 6.7% of members (47.8% White, 67.5% male, mean age: 11.3 ± 3.8 year) were diagnosed with neurodevelopmental disorders: ADHD (5.0%, n = 23,250); ASD (1.1%, n = 5,098); or AuDHD (0.6%, n = 2,665) (all P < 0.0001). Increased odds (i.e., ≥ 2) for certain co-occurring diagnoses were consistently observed across all three neurodevelopmental cohorts for adults and children, which were primarily behavioral health (BH)-related. Compared to those without neurodevelopmental disorders, both adults and children with ASD and/or ADHD had higher healthcare utilization rates [adults: 615.2 to 1024.8 per thousand per month (PTPM); children: 398.4 to 1205.3 PTPM; all P < 0.001)]; largely owing to increased use of BH-related services, translating to greater total healthcare expenditures [adults: $140.3 to $292.1 per member per month (PMPM); children: $50.8 to $845.4 PMPM; all P < 0.001)]. Conclusions Leveraging real-world data of 2,392,855 members from a large national payor, 4.1% of adults and 6.7% of children were diagnosed with ASD and/or ADHD. This population appeared to consistently exhibit specific co-existing diagnoses that frequently co-occur in addition to greater observed healthcare utilization and expenditures. Trial registration Not applicable.